The Impact of Price Perception on Used Car Brand Image at Arengka Automall Pekanbaru - Irfandi, Nazmul; Putri, Librina Tria; Desmawati, Desmawati (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the impact of price perception on the brand image of used cars at Arengka Automall Pekanbaru. The used car industry is characterized by high information asymmetry and perceived risk, making price perception a crucial factor influencing consumer evaluations and brand image formation. A quantitative research approach was employed using a survey method. Data were collected from 200 consumers who had purchased used cars at Arengka Automall Pekanbaru through a structured questionnaire using a five-point Likert scale. The sampling technique applied was purposive sampling. The collected data were analyzed using simple linear regression with the assistance of statistical software. The results indicate that price perception has a positive and significant effect on the brand image of used cars, with a regression coefficient of 0.705 and a significance value below 0.05. This finding demonstrates that consumers who perceive prices as fair, competitive, and commensurate with vehicle quality tend to form a more positive brand image of the used car showroom. The coefficient of determination (R²) shows that price perception explains 49.7% of the variance in brand image, while the remaining percentage is influenced by other factors beyond the research model. This study contributes theoretically by strengthening marketing literature related to price perception and brand image in the context of the used car industry, which has received limited empirical attention. Practically, the findings provide important managerial implications for used car showroom management in designing transparent and value-based pricing strategies to enhance consumer trust and build a sustainable brand image.